Sulfur-Mediated Polycarbonate Polyurethane for Potential Application of Blood-Contacting Materials - Li, Peichuang; Cai, Wanhao; Li, Xin; Zhang, Hong; Zhao, Yuancong; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, a sulfur-mediated polycarbonate polyurethane (PCU-SS) is developed by mimicking the catalyzing ability of glutathione peroxidase (GPx) on nitric oxide (NO) in the human body. The PCU-SS is endowed with the capability to produce NO based on disulfide bonds, which could strongly improve the biocompatibility of the materials. The characterization results indicate that PCU-SS could not only decrease the adhesion of platelets but also enhance the capability of anti-thrombus. Moreover, it is shown that PCU-SS has a good compatibility with endothelial cells (ECs), while has a marked inhibition capacity of the proliferation of smooth muscle cells (SMCs) and macrophages (MA). Meanwhile, the result of animal implantation experiments further demonstrates the good abilities of PCU-SS on anti-inflammation, anti-thrombus, and anti-hyperplasia. Our results offer a novel strategy for the modification of blood-contacting materials based on disulfide bonds. It is expected that the PCU-SS could shed new light on biocompatibility improvement of cardiovascular stents.